Health promotion in school environment in Brazil - Rogério Lessa Horta; Cristine Scattolin Andersen; Raquel Oliveira Pinto; Bernardo Lessa Horta; Maryane Oliveira-Campos; Marco Antonio Ratzsch de Andreazzi; Deborah Carvalho Malta
ABSTRACT OBJECTIVE Evaluate the school environments to which ninth-year students are exposed in Brazil and in the five regions of the country according to health promotion guidelines. METHODS Cross-sectional study from 2012, with a representative sample of Brazil and its macroregions. We interviewed ninth-year schoolchildren and managers of public and private schools. We proposed a score of health promotion in the school environment (EPSAE) and estimated the distribution of school members according to this score. Crude and adjusted odds ratios (OR) were used, by ordinal regression, to determine the schoolchildren and schools with higher scores, according to the independent variables. RESULTS A student is more likely to attend a school with a higher EPSAE in the South (OR = 2.80; 95%CI 2.67-2.93) if the school is private (OR = 4.52; 95%CI 4.25-4.81) and located in a state capital, as well as if the student is 15 years of age or older, has a paid job, or has parents with higher education. CONCLUSIONS The inequalities among the country's regions and schools are significant, demonstrating the need for resources and actions that promote greater equity.